2019
DOI: 10.1093/nar/gkz908
|View full text |Cite
|
Sign up to set email alerts
|

CTCF-dependent chromatin boundaries formed by asymmetric nucleosome arrays with decreased linker length

Abstract: The CCCTC-binding factor (CTCF) organises the genome in 3D through DNA loops and in 1D by setting boundaries isolating different chromatin states, but these processes are not well understood. Here we investigate chromatin boundaries in mouse embryonic stem cells, defined by the regions with decreased Nucleosome Repeat Length (NRL) for ∼20 nucleosomes near CTCF sites, affecting up to 10% of the genome. We found that the nucleosome-depleted region (NDR) near CTCF is asymmetrically located >40 nucleotides 5′-u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 83 publications
4
55
0
Order By: Relevance
“…4b), and this is not an artifact of any averaging process (supplementary note 16). The fact that the length of a structured DNA region exceeds the CTCF consensus motif has been recently reported 64 . As nucleosome formation requires extensive DNA bending, our finding suggests that the sequence-encoded property of CTCF binding sites as being highly cyclizable may favor the formation of nucleosomes.…”
Section: Applications Of the Predictive Model For The Sequence-dependmentioning
confidence: 95%
“…4b), and this is not an artifact of any averaging process (supplementary note 16). The fact that the length of a structured DNA region exceeds the CTCF consensus motif has been recently reported 64 . As nucleosome formation requires extensive DNA bending, our finding suggests that the sequence-encoded property of CTCF binding sites as being highly cyclizable may favor the formation of nucleosomes.…”
Section: Applications Of the Predictive Model For The Sequence-dependmentioning
confidence: 95%
“…First, CTCF is uniquely able to position ~20 nucleosomes around its DNA-binding sites [ 91 95 ], suggesting a mechanism whereby CTCF binding generates a unique chromatin microenvironment that could potentially serve as a steric hindrance pause signal. Consistently, CTCF has been reported to form a highly unusual DNA structure where it binds [ 96 ].…”
Section: One-step Vs Multi-step Ctcf-cohesin Interactions To Explainmentioning
confidence: 99%
“…Third, CTCF is subject to a number of post-translational modifications [ 66 ], some of which are quite large such as SUMOylation [ 98 ] and poly-ADP-ribosylation [ 99 101 ]. Early reports suggested that poly-ADP-ribosylation contributes to the insulation function of CTCF [ 99 , 100 ], and mutation of the 11 amino acids in the N-terminus reported to be poly-ADP-ribosylated as well as treatment with a PARP inhibitor, moderately decreased CTCF’s ability to stabilize cohesin at its binding sites as measured by ChIP-Seq [ 39 ].…”
Section: One-step Vs Multi-step Ctcf-cohesin Interactions To Explainmentioning
confidence: 99%
“…NRL is defined as the average distance (bp) between the dyad axes of adjacent nucleosomes and is traditionally used as an integrative parameter characterizing local nucleosome packing. Previous publications suggest that NRL is different near binding sites of transcription factors [42] and affected by the presence of linker histones, although the role of different H1 variants is not clear [43]. Figure 8 presents normalized calculations of the NRL in regions enriched for the H1 variants, using the NucTools algorithm [27].…”
Section: Influence Of H12/h15 Enrichment On the Nucleosome Repeat Lmentioning
confidence: 99%